Perioperative Nursing Process: reflection on updating the SAEP nomenclature - Gnatta, Juliana Rizzo; Poveda, Vanessa de brito; Ribeiro, Elaine; Duran, Erika Christiane Marocco; Lopes, Camila Takao; Lemos, Cassiane de Santana; Avila, Marla Andreia Garcia de; Fusco, Suzimar de Fátima Benato; Garcia, Taysa de Fátima; Caregnato, Rita Catalina Aquino (FapUNIFESP (SciELO), 2025)
OBJECTIVE: To reflect on the relevance of the Systematization of Nursing Care in the perioperative practice (SAEP) of nurses, comparing it to Resolution No. 736 of 2024 of the Brazilian Federal Nursing Council (COFEN) and proposing the update of its nomenclature to ensure compliance with the aforementioned Resolution. METHOD: This is a reflective study in which experts in perioperative care and/or in Nursing Process (NP) met to discuss the framework named SAEP, adopted by the Brazilian perioperative nurses since the 1990s. Historical aspects of the conceptual framework "Perioperative Nursing Systematics" are discussed, addressing its relevance in the perioperative nurses' practice and comparing it with Resolution No. 736/2024 of the Federal Nursing Council. RESULTS: The SAEP framework proposed in the 1990s is still current in perioperative nursing practice, as it covers the stages of the NP in its entirety. Considering its importance, current status, and applicability in the perioperative nursing practice, parallels are established with the stages of the NP described in Resolution No. 736, suggesting a new nomenclature: Perioperative Nursing Process (PEP). CONCLUSION: An update of the nomenclature from SAEP to PEP is recommended, by aligning the SAEP conceptual framework, COFEN Resolution No. 736 of 2024, and the "Nursing Process" terminology adopted globally.